Efficacy of Decompression Surgery in Malignant Cerebral Edema After Endovascular Thromboembolectomy - Ertugrul, Bilal; Akcin, Ismail; Kaplan, Metin; Erol, Fatih Serhat (Turkish Neurosurgical Soc, 2025)
AIM: To evaluate the outcomes of decompression surgery in patients who developed malignant cerebral infarction after pharmacologic and endovascular thromboembolectomy treatment. MATERIAL and METHODS: The study included 57 patients who underwent decompressive surgery for acute ischemic stroke between 2018 and 2023, having received either pharmacological treatment (intravenous tissue plasminogen activator; group A) or endovascular thromboembolectomy (group B). Age, sex, comorbid chronic diseases, location of thromboembolism at admission, side of ischemia, preoperative Glasgow Coma Scale scores, timing of surgery, and mortality rates were analyzed. The degree of recovery was measured using the modified Rankin Scale (mRS) score at 3 months. RESULTS: The mortality rate after decompression surgery was 48% in group A and 50% in group B. Younger patients had lower mortality rates, with 38% in group A and 50% in group B. When considering all age groups, there was no significant between-group difference in mortality. The mean mRS score was 3.92 in group A and 3.93 in group B, with no significant between-group difference. CONCLUSION: Endovascular thromboembolectomy does not appear to impact mortality and recovery rate in patients undergoing decompression surgery for malignant cerebral edema.
Keywords: Decompressive craniectomy; Cerebral infarction; Middle cerebral artery; Endovascular thrombectomy